Intravenous Immunoglobulin and its Complications - I Mohammadzadeh (Babol University of Medical Sciences, 2011)
Intravenous immunoglobulin (IVIG) is a safe biological product used in many cases, such as primary and secondary immune deficiency, infectious diseases, critically ill patients and autoimmune disorders. IVIG has many advantages compared with intramuscular immunoglobulin and is obtained from pooled plasma of 10.000-60.000 donors. Today, IVIG use in clinical settings has increased. Despite its use in many diseases, FDA only has approved its use in patients suffering from ITP, primary immunodeficiency, pediatric HIV, Kawasaki disease, bone marrow transplantation and B-cells chronic lymphocytic leukemia. But, it has been used for other cases like Guillain–Barré syndrome, premature infants, critically ill patients admitted to ICU, severe asthma and uncontrolled seizures which FDA had not approved yet.This biological product affects immune deficiency and autoimmune diseases in different ways. Despite the relative safety of this product, the patient may experience mild but acute complications.In most cases acute reaction is due to high speed infusion rate which is mild but systemic side effects in the form of allergic and non-allergic anaphylaxis are seen, especially in patients with CVID and IgA selective deficiency. The patient should be under medical supervision during infusion and to deal with anaphylaxis shock, facilities should be available. Today, the subcutaneous type of immunoglobulin is used at home under supervision of a nurse and the patient satisfaction is high, because of its lower cost and also it does not need hospital admission.